Corneal oedema and its medical treatment. (16th May 2013) - Costagliola, Ciro; Romano, Vito; Forbice, Eliana; Angi, Martina; Pascotto, Arduino; Boccia, Tiziana; Semeraro, Francesco
Abstract : Corneal oedema is a common sign of acute or protracted corneal disease of various aetiologies. In this paper, we review the causes and pathophysiological bases of corneal oedema, as well as discussing the goals and modalities of its medical treatment. Corneal oedema, if adequately understood and appropriately treated, generally shows a good prognosis.